2017
DOI: 10.3389/fpsyg.2017.01268
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Positivity-Bias in Children’s Processing of Emotion Terms

Abstract: Emotions play an important role in human communication, and the daily-life interactions of young children often include situations that require the verbalization of emotional states with verbal means, e.g., with emotion terms. Through them, one can express own emotional states and those of others. Thus, the acquisition of emotion terms allows children to participate more intensively in social contexts – a basic requirement for learning new words and for elaborating socio-emotional skills. However, little is kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 61 publications
4
21
0
Order By: Relevance
“…Our finding that children responded more accurately to happy targets parallels previous reports of a “positivity bias” displayed by children on different cognitive tasks (Augusti et al, ; Bahn et al, ; Lewis et al, ). One possible explanation for the facilitation observed with happy emotions is that children are able to process them more efficiently (Todd et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding that children responded more accurately to happy targets parallels previous reports of a “positivity bias” displayed by children on different cognitive tasks (Augusti et al, ; Bahn et al, ; Lewis et al, ). One possible explanation for the facilitation observed with happy emotions is that children are able to process them more efficiently (Todd et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Based on previous findings with children (Lewis et al, 2007), we hypothesized that the manner in which emotions influence cognitive performance in children would be contingent on the valence of the emotion. Specifically, we hypothesized that children would perform better on trials with happy targets than on trials with neutral or angry targets, displaying the "positivity bias" found in previous studies (Augusti et al, 2012;Bahn et al, 2017;Lewis et al, 2007). Following previous findings showing cognitive performance in children to be hampered by negative stimuli (Augusti et al, 2012;Lewis et al, 2007), as well as DCM's prediction that threatening emotions would divert resources away from the cognitive task, we also hypothesized that children would perform worse on trials with angry targets than on trials with happy or neutral targets.…”
Section: Study Goals and Hypothesesmentioning
confidence: 94%
See 1 more Smart Citation
“…In Experiment 2, we looked for effects of embodiment on the categorization of emotion words using a similar task, since a previous study has shown developmental changes in the perception of positive versus negative words using such a task, albeit only in children up to the age of 6 years (Bahn et al, 2017b). Average values of accuracy and response time for correct trials in the congruent and incongruent conditions by children and adults in Experiments 1a and 1b.…”
Section: Methodsmentioning
confidence: 99%
“…To test whether any facial effects of embodiment changed in the course of development, we tested 6-year-old children and adults in Experiment 2 using the same straw-based face manipulation as that in Experiment 1a. The age of 6 was chosen for the children's group because it was the oldest age at which a previous study (Bahn et al, 2017b) was able to find significant effects using the same emotion word categorization task used in this experiment.…”
Section: Methodsmentioning
confidence: 99%